Synergistic effect of bioactive compounds of polyherbal fractions of clinacanthus nutans and elephantopus scaber in the treatment of wound - Aslam, Muhammad Shahzad author (School of Bioprocess Engineering, 2017)
This research was performed to determine the pharmacological profile and their bioactive compounds of herbal extracts in combination, as compared with their individual profile and helps to develop an alternative therapy to treat wound. The use of multiple herbs is common in traditional Chinese and Ayurvedic medicine. The principle of synergistic effect is applicable to the herbal combination. It improves therapeutic efficacy and reduces the unwanted secondary effect. This is in contrast to conventional therapy, where using two or more than two drugs are generally avoided. This suggested the idea of investigating bioactivecompounds from polyherbal fractions that was identified after invitro antioxidant activity and in - vivo wound healing models.